2011
DOI: 10.1111/j.1475-1313.2011.00820.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of background on image recognition in normal vision and age‐related macular degeneration

Abstract: Selective attenuation of the image background can lead to reductions in the bandwidth requirements for image recognition in AMD. However, performance of young normal observers for images presented in the periphery was unlike AMD performance under the conditions investigated. These results have interesting implications for the design of image enhancement algorithms to aid low vision observers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
(129 reference statements)
0
9
0
Order By: Relevance
“…Overall, our findings support previous work suggesting that simplifying visual scenes can be helpful for people with severely impaired vision and show that this approach can be implemented in a see-through head-mounted display. 16 , 17 , 19 , 21 However, our studies indicate that the utility of the current system varies substantially as a function of task. Experiment 1 also suggests that this particular system may not be desirable in all forms of vision loss, both because visual detail from surface texture can be lost and because the resolution of the HoloLens 3D spatial mesh is limited.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Overall, our findings support previous work suggesting that simplifying visual scenes can be helpful for people with severely impaired vision and show that this approach can be implemented in a see-through head-mounted display. 16 , 17 , 19 , 21 However, our studies indicate that the utility of the current system varies substantially as a function of task. Experiment 1 also suggests that this particular system may not be desirable in all forms of vision loss, both because visual detail from surface texture can be lost and because the resolution of the HoloLens 3D spatial mesh is limited.…”
Section: Discussionmentioning
confidence: 82%
“…The augmented reality environment has a simplified visual geometry, with high-contrast edges between objects and surfaces at different distances from the observer, which we hypothesize is more easily interpretable with impaired vision relative to the original view. 16 , 17 , 19 When using the system, the natural field of view is unrestricted, so the appearance is similar to having a window into the augmented reality environment through the HoloLens display (see above). As the user moves around the environment, the colors change to reflect the distances from the current viewpoint.…”
Section: Methodsmentioning
confidence: 99%
“…Boucart et al 7 reported that object categorization was facilitated when objects were located on a homogeneous white background than when the same objects appeared in a scene. In the same line, Bordier et al 32 found a reduction in the spatial frequency bandwidth necessary for image identification when the background was attenuated by lowering its luminance (i.e., the background of the base image was selectively darkened by 80% of its original luminance) both for patients with AMD and for young observers. These results suggest that reduction of crowding improves categorization and identification performance in people who must rely on their peripheral vision.…”
Section: Discussionmentioning
confidence: 90%
“…AMD has been shown to affect processing of high-spatial frequency scenes 64. Moreover, images have been shown to be more recognisable for AMD patients at lower spatial frequency bandwidths if the background is darkened 65. One study asking participants whether or not a real-world target was present in a scene at varying levels of contrast found task success to be strongly related to contrast level 66…”
Section: Resultsmentioning
confidence: 99%